Second allo-SCT in patients with lymphoma relapse after a first allogeneic transplantation. A retrospective study of the EBMT Lymphoma Working Party - Horstmann, Kristin Theres; Boumendil, A.; Finke, J.; Finel, H.; Kanfer, E.; Milone, G.; Russell, N.; Bacigalupo, A.; Chalandon, Y.; Diez-Martin, J. L.; Ifrah, N.; Chacon, M. Jurado; et al. (Bone marrow transplantation, 2015)
The aim of this registry-based retrospective study was to analyze the outcome of second allogeneic hematopoietic SCT (alloHSCT_2) performed in patients with lymphoma who had relapsed after a first allogeneic transplant (alloHSCT_1). Patients ⩾18 years who had received an alloHSCT_2 for lymphoma relapse between 2000 and 2011 were eligible. One hundred and forty patients were identified. The diagnosis was Hodgkin lymphoma (HL) in 31%, diffuse large B-cell lymphoma in 14%, T-cell lymphoma in 12%, indolent lymphoma in 19%, mantle cell lymphoma in 16% and other lymphomas in 8% of the patients. The median interval from alloHSCT_1 to alloHSCT_2 was 19 (range 4-116) months. Disease status at alloHSCT_2 was chemosensitive in 46%, refractory in 43% and unknown in 11% of the patients. Three-year PFS, OS, relapse incidence and nonrelapse mortality were 19%, 29%, 58% and 23%, respectively. PFS and OS were significantly affected by refractory disease at alloHSCT_2 and a short interval between alloHSCT_1 and alloHSCT_2. Long-term PFS was observed across all lymphoma subsets except for aggressive B-cell lymphoma. In conclusion, alloHSCT_2 is feasible and can result in long-term disease control in patients with lymphoma recurrence after alloHSCT_1, in particular if relapse occurs late and is chemosensitive.